Keeping Mental Budgets: Visitors' Spending at a Christmas Market. (February 2015) - Brida, Juan Gabriel; Tokarchuk, Oksana
One of the main concerns of tourism managers lies in stimulating tourists' spending at their destinations. Numerous studies investigating the determinants of tourists' expenditure limit their investigation to the actual expenditure of tourists. This paper extends the existing literature on tourists' spending by introducing mental accounts theory. Mental budgets set the limit on the expenditure on a particular category of goods in order to avoid overspending in situations in which a rational approach to spending is not possible. The authors apply this theory to a case of visitors' spending at a Christmas market in Merano. Data were analysed with the Heckman selection model to understand the determinants of mental budgets and the actual spending of visitors and to study how well their intentions are met by their real behaviour. The findings of the paper indicate that the mental budget is an important component for the analysis of tourists' expenditure.